A UWB bandpass filter with a notched band using dual stepped‐impedance stub‐loaded resonators. Issue 8 (August 2014) - Oh, Sangyeol; Shin, Beomsoo; Jeong, Jichai; Lee, Jaehoon
ABSTRACT In this article, a new notched‐band ultra‐wide bandpass filter (BPF) is proposed, using dual stepped‐impedance stub‐loaded resonators (SISLRs), open‐circuited stubs, and stepped‐impedance ports (SIPs). As dual SISLRs overlay the frequency responses of the two resonators, the in‐band performance of dual SISLRs is better than that of a single SISLR under the same external coupling. Open‐circuited stubs of length λ/4 were placed between dual SISLRs to reject the wireless LAN interference signal band at 5.8 GHz. In addition, we combined SIPs with dual SISLRs for improved passband performance at high frequencies. The proposed filter was validated via simulation and measurement. The measured return loss of the BPF was less than −10 dB throughout the passband of 3.2–11.01 GHz. The group delay remained relatively flat and less than 0.5 ns throughout this passband, except in the notched band. The rejection bandwidth was 5.73–6.31 GHz. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1785–1787, 2014